Relationship Between Duration Of Use Social Media With Quality Sleep For Study Program Students Bachelor Of Nursing Maharani Sticks Poor - Rama Putra Reynaldy; Rahmawati Maulidia; Risna Yekti Mumpuni (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction:The Sleep quality is a state where awareness of something decreases, but brain activity still plays an extraordinary role. Objectives: The purpose of this study was to determine the relationship between the duration of social media use and sleep quality in undergraduate nursing students at STIKes Maharani Malang. Methods: Correlational quantitative research design with a cross sectional approach. The number of research samples is 115 students with simple random sampling technique. Results: The results showed that the value of p = 0.003 which is smaller than α (<0.05). The value of the corelation coefficient (r = 0,272) indicates that there is a relationship between the duration of social media use and the quality of sleep in undergraduate nursing students at STIKes Maharani Malang. Conclusions: The majority or as many as 54 (47.0%) respondents had a moderate duration of social media use among undergraduate nursing study program students at STIKes Maharani Malang. The majority or as many as 98 (85.2%) of respondents experienced poor sleep quality among undergraduate nursing study program students at STIKes Maharani Malang. There is a significant relationship between the duration of social media use and sleep quality in undergraduate nursing study program students at STIKes Maharani Malang with a significance value of p = (0.003) < (0.05) so that the Ha hypothesis decision is accepted, namely that there is a relationship between the duration of social media use with sleep quality in undergraduate nursing study program students at STIKes Maharani Malang.